Perioperative risk factors impact on intensive care unit length of stay (ICU length of stay) in oral squamous cell carcinoma - Abdo Ahmed Saleh Mohamed; Lianxi Mai; Guangxin Rao; Song Fan; Mubarak Ahmed Mashrah; Mohamed Ali Mahyoub Holkom; Chaobin Pan; Zhouyu Lin (BMC, 2023)
Abstract Background The trend in postoperative care for free flap patients is to deescalate from routine ICU admission into a specialty recovery unit. This study aims to investigate the predictive parameters in a routine perioperative clinical assessment that are expected to be directly correlated with prolonged ICU length of stay in at-risk patients who received oral reconstructive surgery for squamous cell carcinoma (OSCC). Methods All patients who underwent ablative surgery for OSCC with free flap reconstruction and were managed in the ICU were included in this study. The primary outcome was ICU-length of stay. Perioperative, operative and postoperative parameters were analyzed using single test ( t-test, ANOVA analysis, correlation coefficients, effect size) and multivariate regression test. The P-value was set as < 0.005 to be considered statically significant. Results The study included 136 homogeneous patients, with a mean ICU length of stay of 4.5 (± 4.43 day). Patients with pre-operative positive renal dysfunction (P = 0.004), peripheral vascular disease (P < 0.001), postoperative complications (P = 0.028) or positive heart failure class III (P < 0.001 ) were recognized as at-risk patients for a significantly longer ICU length of stay. Conclusion Patients with perioperative severe renal dysfunction, peripheral vascular disease, postoperative complication or high NYHA class are prone to have a significantly longer ICU length of stay. Several factors were considered as confounders contributing to increased ICU management time in combination with other variables. Additionally, in highly risk patient, the presence of the highly trained medical support, including the appropriate nursing care, is more critical than those patients without these risk factors.